Analisis Penerapan Business Plan dalam Pengembangan Usaha di UMKM Daerah Sekeloa dan Sukaluyu - Aminullah Paruq Sahubawa; Kania Nurcholisah (Bandung Conference Series: Accountancy, 2023)
Abstract. Entrepreneurs have an important role in building the economy in a country. In the world of the Indonesian economy, MSMEs are the backbone of the economy. Law No. 11 Article 1 of 2020 states that micro, small and medium enterprises (MSMEs) are business activities carried out by individuals, households and small business entities. Identification of the problems in this study are (1) How is the implementation of the business plan in Sekeloa and Sukaluyu UMKM Regions?; and (2) What is the effect of implementing a business plan in business development in Sekeloa and Sukaluyu UMKM Regions?. The object of research is the application of business plans and business development. The research method uses quantitative methods. Data collection techniques using a questionnaire. The total population in this study amounted to 84 SMEs. Determination of the sample using the slovin formula with an error of 15% so that the total sample becomes 30 samples of UMKM. Data analysis on the weight of the questionnaire using a Likert scale. The results obtained in this research are as follows: (1) Of the 30 samples of MSMEs studied, 83% or 25 MSMEs implemented a business plan in developing their business, while 17% or 5 MSMEs did not implement it. This proves that the majority of MSMEs implement business plans in developing their MSME businesses. (2) The application of these aspects to UMKM includes: (a market aspect assessment with a criterion score of 118 is included in the Good category; (b) the assessment of the production aspect shows a criterion score of 128 included in the very good category; (c) the score results the criteria for assessing the MSME management aspect were 124.6 included in the good category, and (4) the score for evaluating the financial aspects was 114.5 included in the good category Abstrak. Wirausaha memiliki peran penting dalam membangun perekonomian di suatu negara . Dalam dunia perekonomian Indonesia, UMKM merupakan tulang punggung perekonomian. Undang-Undang No. 11 Pasal 1 Tahun 2020 menyatakan bahwa usaha mikro kecil menengah (UMKM) merupakan suatu kegiatan bisnis yang dilakukan oleh individu, rumah tangga maupun badan usaha kecil. Identifikasi masalah pada penelitian ini adalah (1) Bagaimana penerapan business plan di UMKM Daerah Sekeloa Dan Sukaluyu?; dan (2) Apa pengaruh penerapan business plan dalam pengembangan usaha di UMKM Daerah Sekeloa dan Sukaluyu?. Objek penelitian adalah penerapan business plan dan pengembangan usaha. Metode penelitian menggunakan metode kuantitatif. Teknik pengumpulan data menggunakan kuesioner. Jumlah populasi dalam penelitian ini berjumlah 84 UMKM. Penentuan sampel menggunakan rumus slovin dengan error 15% sehingga jumlah sampel menjadi 30 sampel UMKM. Analisis data bobot nilai kuesioner menggunakan skala likert. Hasi yang didapat pada peneltiian ini adalah sebagi berikut : (1)Dari 30 sampel UMKM yang diteliti, Sebanyak 83% atau 25 UMKM menerapkan business plan dalam pengembangan usaha mereka, sedangkan 17% atau 5 UMKM tidak menerapkannya. Hal ini membuktikan mayoritas UMKM menerapkan business plan dalam mengembangkan usaha UMKM mereka. (2) Penerapan aspek – aspek tersebut UMKM diantaranya : (a penilaian aspek pasar nilai skor kriteria sebesar 118 termasuk kedalam kategori Baik; (b) penilaian aspek produksi menunjukan nilai skor kriteria sebesar 128 termasuk dalam kategori sangat baik; (c) , hasil skor kriteria penilaian aspek manajemen UMKM sebesar 124,6 termasuk kedalam kategori baik; dan (4) skor kriteria penilaian aspek finansial adalah sebesar 114,5 termasuk kedalam kategori baik.